LOYALITAS EMOSIONAL DAN KETERLIBATAN KOMUNITAS: STUDI KARAKTERISTIK FANATISME PENGGEMAR MUSIK KAPAL UDARA BAND - Nabhan Rizqan Fathana; M. Ramli AT; Ridwan Syam (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2025)
This study analyzes the level of fandom among supporters of Kapal Udara Band in Makassar City through three indicators: imitation, consumptive behavior, and obsession. A descriptive quantitative method was employed, with a sample of 72 respondents selected using Slovin’s technique. Results indicate a "moderate" level of fandom, with a Total Respondent Achievement Rate (TCR) of 53%. Imitation (TCR 55%) and consumptive behavior (TCR 55%) dominated, while obsession scored lower (TCR 48%). Fans tended to be selective in imitating band members and purchasing merchandise, with financial awareness influencing consumption decisions. Obsession manifested as moderate social engagement without disrupting personal lives. These findings align with prior studies highlighting local music fans’ tendency to balance loyalty with personal responsibility. The research concludes that fandom for Kapal Udara Band reflects an integrated collective identity free from extreme dominance, while emphasizing the community’s role in sustaining the local music ecosystem. Practical implications include community-based marketing strategies and strengthening cultural values in the independent music industry.